KEARIFAN LINGKUNGAN MASYARAKAT DESA JATILUWIH : RELEVANSINYA DENGAN PELESTARIAN WARISAN BUDAYA DUNIA - Wiasti, Ni Made (Bumi Lestari, 2016)
Jatiluwih Village and Subak Jatiluwih have been established by the United Nations Educational, Scientific and Cultural Organization (UNESCO) as a part of the World Cultural Heritage (WCH). In addition, the village and the subak (Balinese irrigation cooperative) also have the status as a tourist destination having the potential to conversion of paddy fields. This paper examines the knowledge and understanding of the Jatiluwih Village community on the belief and customs behind the pemali of animal cages in paddy fields, garden in the paddy fields and the merger of paddy field plot activities in the subak area becoming the part of the world cultural heritage, namely the Subak Jatiluwih. In this case, pemali (customary prohibition) along with the belief and customs serving as the background is seen as an environmental wisdom. The conclusion in this paper confirms that the pemali mentioned above are still relevant and important to be understood and actualized in order to preserve the Subak Jatiluwih and to strengthen various regulations having been enacted to protect and preserve the elements of Balinese culture that need protecting and preserving. This strategic measure is to adopt cultural values   contained in the belief and customs that underlie the pemali in the regulations made by relevant government authorities and in bylaws (awig-awig) of the Jatiluwih Customary Village and bylaws (awig-awig) of the Subak Jatiluwih.
Keywords: world cultural heritage, environmental conservation, pemali, subak jatiluwih.